The Effect of Cooperative Learning Model Types of Teams Games Tournament Assisted by Flashcard Media on Student Activity - Widyasari, Emiliasi; Ayatusa’adah, Ayatusa’adah; Rohmadi, Mukhlis (UIN Fatmawati Sukarno Bengkulu, 2022)
The learning that takes place in class VII MTs An-Nur Palangka Raya by looking at the activities of learners in the lessons of science is still less than optimal. Learners feel tired, not feel confident when I asked the teacher to perform in front of the class, even most learners are not reflective of the teacher when learning is in progress. The mood of the class when the lesson science progresses it appears less active for at least students who want to ask and respond to questions, the subject shows the interaction of the learners which is lacking in the learning process. This research aims to know the influence of cooperative learning model type Teams Games Tournament (TGT) berbantu media Flashcard to active learners. This research is a quantitative research method is quasi experiment with research design pretestposttest control group design. The results of data analysis show that the average active learners in the experimental class of 72.62 us% and the control class of 70.00% with good criteria. The results of the analysis of the t-test value of the liveliness of the students of the experimental class obtained Asymp. Sig. (2-tailed) equal to 0.280 > 0.05 then it can be concluded that there is influence of cooperative learning model type TGT-assisted media Flashcard to active learners.